Peran Teknologi Memoderasi Hub Pengetahuan Pajak, Sanksi Pajak Berpengaruh terhadap Kepatuhan Wajib Pajak - Revi Rahmawati; Syaiful Syaiful (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the factors influencing tax compliance among MSME taxpayers in Gresik Regency, focusing on tax knowledge, tax sanctions, and the use of information technology. A quantitative approach was employed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to 97 MSME respondents who met the research criteria. The results showed that tax knowledge and tax sanctions have a positive and significant effect on taxpayer compliance. This indicates that higher levels of understanding of tax regulations and stricter enforcement of sanctions can enhance compliance. However, the use of information technology was found unable to moderate the relationship between tax knowledge or tax sanctions and taxpayer compliance. These findings suggest that although digital systems have been implemented in tax administration, their effectiveness remains limited. Therefore, strengthening tax education and optimizing digital platforms are essential to improve MSME taxpayer compliance sustainably in Gresik Regency.